Contributions of the GPET to the GPAI: tactical context adaptation and game behaviour (Contribuciones del GPET al GPAI: adaptación al contexto táctico y comportamiento de juego) - García López, Luis Miguel; Gutiérrez Diaz del Campo, David (Retos, 2018)
Abstract. The Game Performance Evaluation Tool (GPET) is an instrument that allows us to obtain information about the student's decision-making process during their participation in games. The usual instruments reflect the final result of student's decision. However, the GPET offers an analysis of the context in which the decision has been made, and allows teachers to establish a certain degree of quality in the decision taken. Thus, the GPET helps us to distinguish in the decision-making process, not only "what has been done" from "what should have been done" in a specific game situation (Gutiérrez, González, García-López, Mitchell, 2011), but also it gives us information about the player's adaptation to the tactical context in which he/she is involved during game play. According Godbout (1990), this adaptation to the tactical context describes the decisional process, rather than the result. Given that the GPET is an instrument initially designed for research, in this article we present how to take advantage of the GPET novelties, applying them in an instrument with a clear teaching orientation, such as the Game Performance Assessment Instrument (GPAI) (Mitchell, Oslin and Griffin, 2013).Resumen. El Game Performance Evaluation Tool (GPET, en español Herramienta de Evaluación del Rendimiento de Juego), es un instrumento que nos permite obtener información sobre el proceso de toma de decisiones del alumno durante su participación en los juegos deportivos. Los instrumentos habituales reflejan el resultado final de la decisión del alumno. Sin embargo, el GPET hace un análisis del contexto en el que se ha tomado la decisión, y permite que el docente pueda establecer cierta gradación en la calidad de la decisión tomada. Así, el GPET nos ayuda a distinguir en la toma de decisiones no sólo “qué se ha hecho” de “qué se debería haber hecho” en una situación concreta de juego (Gutiérrrez, González, García-López, Mitchell, 2011), sino también nos aporta información de la adaptación del jugador al contexto táctico en el que se encuentra. Dicha adaptación, de acuerdo con Godbout (1990), nos describe el proceso decisional, más que el resultado. En este artículo presentamos como aprovechar las novedades del GPET, que es un instrumento inicialmente diseñado para el ámbito de la investigación, aplicándolas en un instrumento con una orientación claramente docente, como es el Game Performance Assessment Instrument (GPAI, en español Instrumento de Evaluación del Rendimiento de Juego, de Mitchell, Oslin y Griffin, 2013).